2017
DOI: 10.1051/matecconf/201712905001
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic formwork used in strengthening of structural elements during reconstruction of buildings and structures

Abstract: Abstract. The paper discusses the importance of building reconstruction and the need for improving the available formwork systems used for strengthening of structural elements during reconstruction. Citing the results of the analysis of the Russian and foreign scientific publications, the authors emphasize the necessity of replacing costly wooden formworks with high-technology reusable all-purpose and mobile formwork systems. Considering that such requirements are met by rubber-fabric formworks, the authors ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Considering that the modern forming systems used to strengthen structural elements are most commonly made of expensive materials (wood, metal) and should be replaced with their more economical counterparts, a hypothesis arose featuring artificial wood as the decking (board) material for the suggested transformer decking. Previously, the need for use of innovative technologies in the reconstruction of buildings and works was dicussed by the authors in [9,22].…”
Section: Goal Tasks Methods Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that the modern forming systems used to strengthen structural elements are most commonly made of expensive materials (wood, metal) and should be replaced with their more economical counterparts, a hypothesis arose featuring artificial wood as the decking (board) material for the suggested transformer decking. Previously, the need for use of innovative technologies in the reconstruction of buildings and works was dicussed by the authors in [9,22].…”
Section: Goal Tasks Methods Of Studymentioning
confidence: 99%
“…The relevance of the selected topic is associated with an increasing scope of reconstruction of buildings and works, being one of the main aspects of sustainable development of urban space [1][2][3] and provision of housing [4][5][6] for urban population. The rationality and comfort of municipal and any other residential environment are a function of improved performance parameters (also accomplished through overhaul) and enhanced operational and environmental safety of existing buildings and works [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the PERI system formwork can minimize costs because it does not use a lot of labor. The labor intensity in the installation and disassembly of formwork is much lower than conventional wooden formwork [31]. Installing the PERI formwork system is relatively easy, producing high productivity.…”
Section: Cost Analysismentioning
confidence: 99%
“…They presented construction approaches and design methodology too. Abramyan et al (2017) described the design, installation, and dismantling techniques of a reusable multipurpose mobile pneumatic rubber-fabric formwork systems. They showed that installation and dismantling of such formworks are much easier than conventional formworks.…”
Section: Form Findingmentioning
confidence: 99%